MOBILISING THE SCIENTIFIC COMMUNITY - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Decentralised land tenure management has been the topic of several international meetings in the last five years. It came to the fore during a conference of the Permanent Interstate Committee for Drought Control in the Sahel (CILSS) and the Club de...